(untitled) (Research, Society and Development, 2020)
The present study aims to analyze the evolution of the Human Development Index and the effective actions of public policies in the interregnum from 1991 to 2010, in the municipality of Sousa-Paraíba. In this perspective, this article, through descriptive research, of qualitative nature, deductive method, collection of documentary and bibliographic data, proceeded in order to carry out a detailed analysis of the increase in Sousa’s Human Development Index, in order to ascertain the performance of this municipality in relation to its federative, regional and state context in the period from 1991 to 2010, as well as to investigate how the resource allocations and implementation of actions by public managers contributed to the evolution of Sousa’s MHDI. Nevertheless, it also elucidated the increase in the MHDI related to the municipality’s economic context. For this purpose, the values of the Gross Domestic Product were used, seeking to identify whether there was a proportional increase in the two indexes. Finally, in view of the exposed problem, it was sought to clarify the need for the State, based on the defense of basic rights and respect for the well-being of the population, to implement public policies that aim to promote social equity, making it possible to improve the job offer, professional qualification, poverty eradication, in addition to good quality health and education, as well as public security, leisure and basic sanitation, in view of the substantial inconveniences caused to the Democratic Rule of Law by failure to observe these guarantees.